Mary Wollstonecraft and Mary Shelley : writing lives - Buss, Helen M.; Macdonald, David Lorne, 1955-2010; McWhir, Anne, 1947- (Wilfrid Laurier University Press, 2001)
Pioneers in life writing, Mary Wollstonecraft, author of A Vindication of the Rights of Woman (1792), and Mary Shelley, author of Frankenstein (1818), are now widely regarded as two of the leading writers of the Romantic period. They are both responsible for opening up new possibilities for women in genres traditionally dominated by men. This volume brings together essays on Wollstonecraft's and Shelley's life writing by some of the most prominent scholars in Canada, Australia, and the United States. It also includes a full-length play by award-winning Canadian playwright Rose Scollard. To.